2023
DOI: 10.1002/anie.202217378
|View full text |Cite
|
Sign up to set email alerts
|

Ultra‐Fast Preparation of Large‐Area Graphdiyne‐Based Membranes via Alkynylated Surface‐Modification for Nanofiltration

Abstract: Graphdiynes (GDYs), two-dimensional graphene-like carbon systems, are considered as potential advanced membrane material due to their unique physicochemical features. Nevertheless, the scale-up of integrated GDY membranes is technologically challenging, and most studies remain at the theoretical stage. Herein, we report a simple and efficient alkynylated surface-mediated strategy to prepare hydrogen-substituted graphdiyne (HsGDY) membranes on commercial alumina tubes. Surface alkynylation initiates an accelera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…[ 41 ] The presence of carbon‐oxygen bonds indicated by XPS can be explained to be a consequence of the chemical adsorption of oxygen molecules onto the surface of the Bi‐HsGDY due to exposure to atmospheric moisture. [ 42 ] Also, to confirm the complete etching of Ge by chemical agents and to rule out the presence of any Ge contamination in the Bi‐HsGDY, Raman intensity maps were obtained for the Ge peak which is located at 292 cm −1 . Raman mapping showed that the Ge etching process was perfectly accomplished and the Bi‐HsGDY was free of contaminants (Figure S6, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…[ 41 ] The presence of carbon‐oxygen bonds indicated by XPS can be explained to be a consequence of the chemical adsorption of oxygen molecules onto the surface of the Bi‐HsGDY due to exposure to atmospheric moisture. [ 42 ] Also, to confirm the complete etching of Ge by chemical agents and to rule out the presence of any Ge contamination in the Bi‐HsGDY, Raman intensity maps were obtained for the Ge peak which is located at 292 cm −1 . Raman mapping showed that the Ge etching process was perfectly accomplished and the Bi‐HsGDY was free of contaminants (Figure S6, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…Actinide ions on the graphdiyne had different coordination patterns and adsorption capacities, resulting in the separation of these ions commonly found in nuclear fuel (Figure j) . On the separation of small organic molecules in water, the superhydrophilic surface and hydrophobic pore membrane have been fabricated by Meng and co-workers (Figure k) . The HsGDY membrane with continuous stability could realize an excellent water permeance rate (near 1100 L m –2 h –1 MPa –1 ; Figure l–n).…”
Section: Other Applications Of Graphdiyne-based Materialsmentioning
confidence: 99%
“…(n) Permeance and rejection rates of different conditions. Reproduced with permission from ref . Copyright 2023, Wiley-VCH.…”
Section: Other Applications Of Graphdiyne-based Materialsmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] In the next 13 years, the research results related to graphdiyne have increased year by year. Compared with other all-carbon materials, graphdiyne with advantages in controllable growth [2,6,[9][10][11][12] exhibits great potential in promoting innovative development in many fields such as catalysis, [4,[13][14][15][16][17][18][19][20][21][22][23][24][25] photoelectric conversion, [13,15,[26][27][28][29][30] energy storage, [5,[31][32][33][34][35][36][37] separation, [38][39][40] wearable electronics [41][42] and other fields. [43]…”
Section: Introductionmentioning
confidence: 99%